2010
DOI: 10.1016/j.ijid.2010.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Circulating concentrations of α- and β-chemokines in neonatal sepsis

Abstract: Our findings suggest up-regulation of GRO-α and down-regulation of RANTES at the onset of a septic episode, similar to the response pattern observed in septic adults. Both term and preterm neonates appear to have the potential to elicit a chemotactic response to infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
1
7
1
Order By: Relevance
“…For instance, in a study of multiple myeloma that used an ELISA system, control values (in pg/mL) for epithelial neutrophil-activating protein-78 (ENA-78), GRO-α, HGF, and vascular endothelial growth factor (VEGF) ranged higher than in our control patients [7,8]. The same trend was reported in neonatal studies with that system [9].…”
Section: Discussionsupporting
confidence: 69%
“…For instance, in a study of multiple myeloma that used an ELISA system, control values (in pg/mL) for epithelial neutrophil-activating protein-78 (ENA-78), GRO-α, HGF, and vascular endothelial growth factor (VEGF) ranged higher than in our control patients [7,8]. The same trend was reported in neonatal studies with that system [9].…”
Section: Discussionsupporting
confidence: 69%
“…Taking into account the fact that in healthy children serum levels of IL-17 increase with age [28], low or undetectable IL-17 levels observed in neonates may mirror the immaturity of the neonatal immune system to launch an effective Th17 response. Most of the previous studies showed lower RANTES concentration in septic neonates compared with healthy subjects [19][20][21][22], though diametrically opposite results have also been reported in the setting of EONS [23]. In the current study the median concentration of this chemokine was lower in EONS group then in non-infected neonates, but the difference did not reach statistical significance.…”
Section: C5a (Ng/ml) Rantes (Ng/ml)contrasting
confidence: 84%
“…An inverse correlation has been reported between the levels of RANTES and disease severity, and mortality in patients with sepsis and lower levels of this chemokine were found in non-surviving patients, suggesting its beneficial pro-inflammatory role in host response to infection [18]. A few studies reported RANTES levels in infected neonates [19][20][21][22] including those with EONS [20,22]. Most of them documented lower RANTES levels in infected neonates compared to non-infected controls.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that serum CXCL13, CXCL1, CXCL2, CXCL5, CXCL6, CXCL8, CXCL16, CCL27, CCL2, CCL8, CCL3, CCL20, CCL23, CCL27, and CX3CL1 levels were signi cantly increased in neonates with sepsis compared to those in the control group. Manoura et al also found that the levels of serum CXCL1 and CXCL5 were higher in neonates with sepsis [18]. Among these chemokines, CXCL1, CXCL2, CXCL5, CXCL6, and CXCL8 are potent chemoattractants for neutrophils.…”
Section: Discussionmentioning
confidence: 93%